THE EFFECTIVENESS OF COOPERATIVE LEARNING MODEL NUMBERED HEADS TOGETHER (NHT) TYPE AND TALKING STICK TYPE OF STUDENTS IN SMP NEGERI 3 SENTOLO - Dwi Solikhatun; Edi Prajitno (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2017)
In SMP Negeri 3 Sentolo, the learning activities tend to teacher learning-centered, it causes boredom and tiring of students. This can affect student learning results. One can be applied to solve this problem as an alternative learning model is a cooperative learning model NHT type and Talking Stick type. Therefore the purpose of this study is to determine the effectiveness of cooperative learning model NHT type and Talking Stick type of VII students in SMP Negeri 3 Sentolo Kulonprogo on even semester in the academic year of 2015/2016. The population in this study were all students of class VII SMP Negeri 3 Sentolo Kulonprogo academic year 2015/2016. That is consisting of six classes with 168 students. The samples were taken two classes used random technique sampling for each class. It is obtained VII A as the experimental class I and VII C as the experimental class II. The data analysis technique used a prerequisite test. It includes a normalized test, homogeneity test, and hypothesis test of two parties and one party. Based on the calculation of the two parties hypothesis test with significance level a = 5% and 56 degrees of freedom obtained value  and  so ,  then accepted H0 means there is no difference in the students' mathematics learning result which uses cooperative learning model NHT type and Talking stick type. On the other hand, for one party  hypothesis test with significance level a = 5% and 56 degrees of freedom is obtained  and  so , then accepted H0 it means both cooperative learning model NHT type and Talking stick type no more effective than the other one.